CAPITAL STRUCTURE AND PROFITABILITY: THE MACEDONIAN CASE - Ferati, Rametulla; Ejupi, Elsana (European Scientific Journal, ESJ, 2012)
The determination of a company’s capital structure constitutes a difficult decision, one that involves several and antagonistic factors, such as risk and profitability. That decision becomes even more difficult, in times when the economic environment in which the company operates presents a high degree of instability. Therefore, the choice among the ideal proportion of debt and equity can affect the value of the company, as much as the return rates can. In the present study, the authors tried to examine the influence of the capital structure of Macedonian companies regarding the factor profitability. The necessary data, which are used in this work are the financial reports provided by the 150 respective firms collected in the past ten years. The Ordinary Least Squares (OLS) method was employed in the estimation of a function relating the return on the equity (ROE) with the indexes of long and short-run debts, and also with the total of owner’s equity. The results indicate that the return rates present a positive correlation with short-term debt and equity, and an inverse correlation with long-term debt.